THE INFLUENCE OF IMPORT EXPORTS ON ECONOMIC GROWTH FROM AN ISLAMIC PERSPECTIVE - Amelia, Devi; Fauziyah, Firnanda (ISTISMAR, 2023)
The significance of promoting exports in order to boost national income and promote economic growth. The community grows rich as economic income rises. Additionally, exporting helps the nation create foreign exchange, which is subsequently utilized to fund its needs for development. The high rate of economic growth that can be attained through import and export operations is a sign of a successful and well-represented nation. Islam's perspective on the economy is based on the actions of the Prophet Muhammad SAW, his relatives, and associates who engage in cross-border trade in the Arabian Peninsula, Yemen, Bahrain, Syria, and other border regions. The issue occurs when exports prove to be less than imports, which results in a negative trade balance, a drop in the value of the currency, and a reduction in people's purchasing power, all of which have an impact on economic growth. Using the literature review method, this essay will examine how imports and exports affect economic growth from an Islamic perspective.